Comparative morphometrics of Anas ducks, with particular reference to the Hawaiian Duck Anas wyvilliana, Laysan Duck A. laysanensis, and Eaton’s Pintail A. eatoni - Livezey, Bradley C (Wildfowl, 1993)
The Hawaiian Duck or Koloa, Laysan Duck, and Eaton’s Pintail were compared morphometrically with their continental relatives, and the three insular endemics were found to be 19-59% less massive than their continental relatives. External dimensions showed similar decreases in insular species, whereas sexual dimorphism of most external measurements was similar in insular and continental groups. Relative wing size was slightly smaller in the Hawaiian Duck and moderately smaller in the Laysan Duck than in continental mallards; relative wing size of Eaton’s Pintail was similar to that of the Northern Pintail. Canonical analyses of external measurements revealed that the Hawaiian Duck and Laysan Duck differed from the Common Mallard primarily in relative lengths of the bill and wing, whereas Eaton’s Pintail had relatively shorter bills and longer tails than the Northern Pintail. Relative depth of the carina sterni was smaller in the Hawaiian Duck and the Laysan Duck than in continental mallards; relative carina depth was equal in the Northern and Eaton’s Pintails. Wing elements of Hawaiian Ducks and Laysan Ducks were shorter (particularly distally) than those of continental relatives. Skeletal elements of the leg were shorter in the two insular mallards; in Hawaiian Ducks, the tibiotarsus is disproportionately short and distal elements long whereas in the Laysan Duck the femur was disproportionately long and the tarsometatarsus and middle toe disproportionately short. Canonical analysis of complete skeletons of mallards confirmed that the Laysan Duck and (to a lesser extent) the Hawaiian Duck differed from continental species by their disproportionately small skulls, distally shortened wings, relatively small pectoral and pelvic girdles, and variably altered proportions within the leg. The morphological peculiarities of Hawaiian Duck, Laysan Duck, Eaton’s Pintail, and other insular dabbling ducks (including subfossil species) are considered with respect to pectoral reduction, feeding ecology, parameters of reproduction correlates of body mass, ontogeny, population size, and the extinction of dabbling ducks endemic to oceanic islands.